Rational antihypertensive therapy in patients with obstructive sleep apnea - M. V. Gorbunova; S. L. Babak; A. G. Malyavin (SINAPS LLC, 2019)
Background. The relationship between obstructive sleep apnea (OSA) and hypertension (AH) is well known. In numerous studies it was found that obstructive sleep apnea was an independent predictor of the development of resistant AH (RAH), and the severity of apnea was directly correlated with the severity of RAH with the exception of the such confounders as age, obesity, sex.The purpose of this publication is to present a new strategy and modern approaches of drug and non-drug therapy of resistant hypertension in patients with OAS with the possibility of their implementation in real clinical practice.Conclusion. Currently, for a practitioner, the therapy of the patient with OSA and RAH is a serious clinical problem. A new rational therapeutic strategy for the treatment of such patients includes a combination of three-component drug therapy and non-drug continuous positive air pressure therapy (CPAP therapy). A reasonable duration of CPAP therapy should exceed 12 weeks. The proposed strategy for the treatment of patients with OAS+RAH has the highest efficiency of achieving blood pressure levels and significantly reduces the risks of fatal cardiovascular events.